Gen-Z Perspective of Second Account Pseudonym Usage on Instagram Ap-plication in Student Identity Formation - Purnamasari, Ita; Sinta, Nuria; Refinita, Nanda Ayu (Insan Akademika Publications, 2025)
This study examines Gen-Z's view of using the second ac-count pseudonym (a pseudonym on the second account) on the Instagram application as a place to shape the identity of students. This study was conducted in a qualitative descriptive method using interview techniques. The population in this study is the result of a live interview with a source who focuses on Instagram applications. The source we chose was Gen-Z, a student at PGRI University Wiranegara Pasuruan, the 2022 class of Pancasila and Citizenship Education Study Program, because Gen-Z is a generation that grows with technology that makes them more proficient in using digital platforms than generations - previous generations . In the formation of identity, researchers found a view from Gen-Z that considers that one of the platforms that can be used as self-disclosure is through a pseudonym second account on the In-stagram application. the use of a second account is based on the existence of a person's self-limitation on the surrounding people who want to be covered with the aim of not knowing the other side that the person has, seocnd account is made by someone so that they are able to express themselves without worsening the existing image. Pseudonym second account in the Instagram application is a separate space for generation Z to show another side that cannot be known to the general public. the existence of a second account on the Instagram application for Pancasila and Citizenship Education Students of PGRI Wiranegara University as a strategy to shape identity, privacy and self-control in the digital world. This research can expand the understanding of digital identity dynamics and how technology shapes human behaviour. For practitioners, such as psy-chologists, educators, and policy makers, this research can provide insights into how social media use affects the identity and behaviour of university students, so that it can help them develop ef-fective intervention strategies to support healthy and positive identity development. In addition, this study can also contribute to the development of theories and models about digital identity and online behaviour, which can be used as a reference for further research and professional practice